EXAMINING THE CONDITIONS AND BARRIERS FOR WOMEN AND GIRL CHILDREN IN TELANGANA'S UNORGANIZED WORKFORCE - Koluguri, Sarika; Prof. D. Sreeramulu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Purpose: This study aims to comprehensively examine the conditions and barriers faced by women and girl children in Telangana's unorganized workforce. It seeks to explore the status of working conditions, health, and vulnerabilities specific to this demographic, providing nuanced insights into their experiences. Additionally, the research identifies and analyzes barriers hindering their access to education, healthcare, and social welfare due to their engagement in the unorganized sector. Methodology: The study employs a qualitative and exploratory approach, utilizing primary data collected through convenient sampling from 127 participants within Telangana's unorganized workforce. Data analysis includes statistical tools such as Discriminant Analysis and Exploratory Factor Analysis to gain in-depth insights into the challenges faced by women and girl children in this sector. Findings: The findings underscore the complex interplay between health support initiatives from employers and the overall well-being of women and girl children in Telangana's unorganized workforce. While positive correlations exist between favorable working conditions and work-life balance, persistent concerns about workplace safety highlight the need for enhanced safety measures. Despite moderate job security perceptions, the significant barriers in accessing social security benefits reveal underlying economic vulnerabilities. Educational challenges, such as discrimination at schools, coupled with limited utilization of government healthcare schemes, further emphasize the systemic hurdles faced by this demographic in accessing essential services. Conclusion: The study concludes that targeted interventions are crucial to improve conditions for women and girl children in Telangana's unorganized workforce. Priority actions include strengthening workplace safety regulations, enhancing accessibility to government healthcare schemes, and addressing educational discrimination. Streamlining access to social security benefits and fostering collaborative efforts involving local communities, employers, and governmental and non-governmental organizations are essential for effective implementation of recommendations and holistic support for this workforce.